BOShLANG’ICh SINFLARDA ONA TILI DARSLIGINING YaRATILIShI VA O’QITILIShINING ILK BOSQIChLARI XUSUSIDA - Ermatov, I.; Turdieva, R. (SCIENCE and SOCIETY, 2021)
The article discusses the first textbooks on the subject of native language at primary school, as well as the need for this textbook and the initial research. The aim of the research is to study the educational process based on the creation of the first textbooks in primary school.